Major and trace element analyses of diabase dykes from Häme area, Southern Finland (IEDA: EarthChem Library)
The Häme diabase dyke swarm (ca. 1.64 Ga) is located in the Svecofennian domain of the Fennoscandian Shield in southern Finland. The data consists of 69 geochemical samples representing 66 dykes. Block samples of 44 dykes were taken in 2008 and 22 dykes were sampled with a portable drill during paleomagnetic field campaigns in 2009, 2014, and 2016. The subset of 22 drillcore samples was analyzed with a PANalytical Axios mAX WDXRF spectrometer. The 44 block samples were analyzed for major and trace elements using a Philips PW1480 Xray spectrometer and for trace elements (REE, Ba, Th, Nb, Y, Hf, Ta, U, Pb, Rb, Cs, Sr, Sc, Zr) using an inductivelycoupled plasma source mass spectrometer (ICPMS) at the Peter Hooper GeoAnalytical Laboratory, University of Washington.